2018
DOI: 10.1103/physrevb.97.094424
|View full text |Cite
|
Sign up to set email alerts
|

Spin-wave beam propagation in ferromagnetic thin films with graded refractive index: Mirage effect and prospective applications

Abstract: Using analysis of iso-frequency contours of the spin-wave dispersion relation, supported by micromagnetic simulations, we study the propagation of spin-wave (SW) beams in thin ferromagnetic films through the areas of the inhomogeneous refractive index. We compare the transmission and reflection of SWs in areas with gradual and step variation of the SW refractive index. In particular, we show the mirage effect for SWs with narrowing SW beam width, and an application of the gradual modulation of the SWs refracti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
0
25
0
2
Order By: Relevance
“…To change the wave number and thus the index for the given wave frequency, we need to change the dispersion relation by varying one of the bulk material parameters, or film thickness [11][12][13][14][15] . We then need to choose an isotropic dispersion relation that enables a large change in k, and thus n. This requirement is satisfied in the dipolar-dominated regime, in the forward-volume geometry, where the magnetization is directed normal to the film plane.…”
Section: Theory Of Spin Wave Steering Lensesmentioning
confidence: 99%
See 1 more Smart Citation
“…To change the wave number and thus the index for the given wave frequency, we need to change the dispersion relation by varying one of the bulk material parameters, or film thickness [11][12][13][14][15] . We then need to choose an isotropic dispersion relation that enables a large change in k, and thus n. This requirement is satisfied in the dipolar-dominated regime, in the forward-volume geometry, where the magnetization is directed normal to the film plane.…”
Section: Theory Of Spin Wave Steering Lensesmentioning
confidence: 99%
“…However, these waveguides may suffer from losses/scattering in bends, and usually have a large spatial footprint. An alternative solution is to steer spin waves via a graded refractive index [11][12][13][14] , which smoothly alters the wave trajectory with minimal reflections 15 . To achieve a graded index for spin waves, one must gradually change a magnonic parameter on a length scale much smaller than the wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…A main aspect of this confinement at relatively low frequencies is the formation of a caustic beam [10][11][12]. Additionally, it has been shown that refractive spin-wave optics can be realized [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Сегодняшняя тенденция к уменьшению размеров устройств обработки информации, использующих волновые процессы в ферритах, требует обращения к нанометровому диапазону длин магнитостатических волн [1][2][3][4]. В этом плане на смену довольно длинных (десятки и сотни микрон) дипольных волн [5][6][7][8] ожидается пришествие коротких (десятки и единицы нанометров) волн обменного характера [9,10], в том числе терагерцового диапазона, возбуждаемых импульсами фемтосекундной длительности [11][12][13] ( (3)…”
Section: Introductionunclassified